2008
DOI: 10.1371/journal.pgen.1000010
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Yellow Skin Gene Reveals a Hybrid Origin of the Domestic Chicken

Abstract: Yellow skin is an abundant phenotype among domestic chickens and is caused by a recessive allele (W*Y) that allows deposition of yellow carotenoids in the skin. Here we show that yellow skin is caused by one or more cis-acting and tissue-specific regulatory mutation(s) that inhibit expression of BCDO2 (beta-carotene dioxygenase 2) in skin. Our data imply that carotenoids are taken up from the circulation in both genotypes but are degraded by BCDO2 in skin from animals carrying the white skin allele (W*W). Surp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
267
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(285 citation statements)
references
References 33 publications
15
267
1
2
Order By: Relevance
“…The scale of human selection on tropical forest species can be seen in the number of them that are central to global cuisine today, including sweet potato, manioc, chilli, black pepper, mango, yams, pineapple and banana 64 (Figure 3). While domesticated tropical forest fauna are fewer in number, the now globally-distributed domestic chicken also most likely had a tropical forest origin in the form of the jungle fowl 65 . Despite new crops, however, increasingly settled tropical forest communities also continued to practice the same agro-forestry systems developed by their forebearers, focused on the management of various tree species.…”
Section: Farming In the Forestmentioning
confidence: 99%
“…The scale of human selection on tropical forest species can be seen in the number of them that are central to global cuisine today, including sweet potato, manioc, chilli, black pepper, mango, yams, pineapple and banana 64 (Figure 3). While domesticated tropical forest fauna are fewer in number, the now globally-distributed domestic chicken also most likely had a tropical forest origin in the form of the jungle fowl 65 . Despite new crops, however, increasingly settled tropical forest communities also continued to practice the same agro-forestry systems developed by their forebearers, focused on the management of various tree species.…”
Section: Farming In the Forestmentioning
confidence: 99%
“…The yellow skin colour is the result of the expression of carotenoid pigments in the skins of birds (Smyth, 1990). According to Eriksson et al (2007), it is generally considered to be associated with the individual's adaptive fitness that reflects its nutritional status or health that is indicative of its foraging efficiency and immune status.…”
Section: Morphological Variationsmentioning
confidence: 99%
“…Similarly, the presence or absence of the carotenoid pigments, primarily xanthophylls, in the feed is responsible for the diversity in skin colour of chickens. The genetic basis of this variation was described by Eriksson et al (2007).…”
Section: Introductionmentioning
confidence: 99%
“…Red Junglefowl still commonly exist in their native habitats (Brickle et al., 2008; Brisbin, 1995) and are clearly distinguishable from domestic chickens (Johnsgard, 1999). Although genetic contributions from multiple Junglefowl species may have played a role in the domestication process (Eriksson et al., 2008; Nishibori, Shimogiri, Hayashi, & Yasue, 2005), archeological and genetic evidence (Fumihito et al., 1994, 1996; Gongora et al., 2008; Storey et al., 2012; Thomson et al., 2014) indicate that Red Junglefowl from Southeast Asia was the primary progenitor of all domestic breeds of modern chickens. In a previous study, we identified substantial haplotype variation in the major histocompatibility complex (MHC) B‐locus of wild Red Junglefowl (Fulton et al., 2016; Nguyen‐Phuc, Fulton, & Berres, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Most, if not all, recent genetic studies involving junglefowl, however, sample birds from captive colonies (e.g., Berthouly et al., 2009; Eriksson et al., 2008; Fumihito et al., 1994; Gering, Johnsson, Willis, Getty, & Wright, 2015; Mekchay et al., 2014; Moiseyeva, Romanov, Nikiforov, Sevastyanova, & Semyenova, 2003; Romanov & Weigend, 2001; Rubin et al., 2010; Tadano et al., 2008; Worley et al., 2010) or from vaguely described geographic localities (e.g., Akaboot, Duangjinda, Phasuk, Kaenchan, & Chinchiyanond, 2012; Granevitze et al., 2007; Liu et al., 2006; Miao et al., 2013; Nishibori et al., 2005; Okumura et al., 2006; Ulfah et al., 2016). Even the female Red Junglefowl individual used for the Gallus gallus reference sequence (International Chicken Genome Sequencing Consortium, 2004) is traceable to the San Diego Zoo, itself believed to be introgressed with White Leghorn alleles (M. E. Delany, University of California, Davis, CA, personal communication).…”
Section: Introductionmentioning
confidence: 99%